Pengetahuan Pubertas Normal dan Siklus Menstruasi Remaja - C. Ermayani Putriyanti; Eka Ratnawati (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2019)
The degree of understanding of puberty is still very varied. It has an impact on the cleanliness of erroneous menstruation, which will have long-term effects on reproductive health. The study aims to identify adolescent knowledge about normal puberty and menstrual cycles. This research was a quantitative study of observational approach by using the knowledge survey of normal puberty and the menstrual cycle involving 55 students of State Junior High School (SMPN) 1 Parakan, Temanggung, Central Java. The technicality used descriptive statistics. The results of this study revealed that knowledge of the degree of normal paper and the menstrual cycle was still low (21.33%). The main sources of information about puberty and menstruation are thousands (85.5%). Teenagers do not know about the interval between the onset of puberty and menarche (87%), few adolescents understand the first sign of puberty (33%). Most teenagers have understood the normal menstrual cycle correctly (78%). There was no significant relationship between knowledge of the first sign of puberty with respondents' understanding of belief. Meanwhile, there was a significant relationship between menstrual status and knowledge about the menstrual cycle and the number of replacement pads. The results showed that students have a poor understanding of puberty, hence, health education must be given to students and their parents.